2020
DOI: 10.1158/1078-0432.ccr-20-0951
|View full text |Cite
|
Sign up to set email alerts
|

Early Relapse Risk in Patients with Newly Diagnosed Multiple Myeloma Characterized by Next-generation Sequencing

Abstract: Writing-review and editing: all the authors All the authors approved the final version of the manuscript and agreed to be accountable for all aspects of the work in ensuring that questions related to the accuracy or integrity of any part of the work are appropriately investigated and resolved.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…IGLL5 located within the immunoglobulin lambda locus encoded one of the IGLLs, which were the immunoglobulin lambda joining 1 and the immunoglobulin lambda constant 1 gene segments. Only a limited number of research has shown that IGLL5 has a frequent mutation in chronic lymphocytic leukemia [33,34], lymphoma [35][36][37], and multiple myeloma [38,39]; besides, IGLL5 has a prognostic value in several diseases, such as multiple myeloma and glioblastoma [39][40][41]. Moreover, previous studies have shown that IGLL5 has a prognostic value in ccRCC, while no in-depth study has concentrated on TICs.…”
Section: Discussionmentioning
confidence: 99%
“…IGLL5 located within the immunoglobulin lambda locus encoded one of the IGLLs, which were the immunoglobulin lambda joining 1 and the immunoglobulin lambda constant 1 gene segments. Only a limited number of research has shown that IGLL5 has a frequent mutation in chronic lymphocytic leukemia [33,34], lymphoma [35][36][37], and multiple myeloma [38,39]; besides, IGLL5 has a prognostic value in several diseases, such as multiple myeloma and glioblastoma [39][40][41]. Moreover, previous studies have shown that IGLL5 has a prognostic value in ccRCC, while no in-depth study has concentrated on TICs.…”
Section: Discussionmentioning
confidence: 99%
“…In a multivariate analysis, D'Agostino et al showed that mutation of P53 was correlated with early relapse in MM patients. In addition, the study showed that patients with both, deletion of the 17p and P53 mutations, have a shorter OS compared to patients with only one chromosomal aberration [15]. An increased risk of acquired P53 mutation was also observed in patients carrying a deletion of 17p [15].…”
Section: Introductionmentioning
confidence: 89%
“…For instance, intermediate-fit or frail patients may safely receive naked mAbs or ADCs, but they are unlikely to tolerate BiAbs or CAR T-cell therapy. On the other hand, fit patients who present with high-risk disease or who experienced early relapse after first-line treatment may benefit from BiAbs or CAR T-cell therapy [101]. As with anti-CD38 therapies, the mechanisms of resistance to anti-BCMA agents may shed light on the optimal treatment sequencing.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%